Avaliação da qualidade da ostra nativa Crassostrea brasiliana congelada em concha em função da composição química e análise sensorial - Portella, Carolina de Gasperi [UNESP] (2005)
Oyster fanning appeared of the necessity in taking care of the increasing- demand of oysters, without threatening the natural supply through the extrativism. The farming had been improved to long of the years in diverse countries allowing a increase the production of this mollusc. Increase of the production is being incompatible to the consumed volume in natura, and as consequence, becomes necessary the perfectioning of the technology after¬ harvest. To reach such objective, the freezing of entire oysters (alive) in continuous air blast freezer was carried through. The changes of chemical composition, condition indices and sensorial tests were analyzed in response to different samples of oysters: fresh and frozen, with O (just frozen), 30 and 60 and 90 days. The chemical composition of the fresh oyster showed average texts of moisture of 81.71 ± 0.56 and 83.25 ± 0.12; of protein of 9.96 ± 0.48 and 11.02 ± 0.59; lipid of 0.51 ± 0.11 and 0.27 ± 0.14; carbohydrate of 6.06 and 3.22, for the I and II experiment, respective1y. Relating to the processing of the oyster, alterations in its chemical composition, as much in function of the freezing as of the storage had been detected, in both experiments. The studied indices of condition had shown to differences between the fresh oysters and the frozen ones, and in general way they are in accordance with the described va1ues in literature. With the sensorial analysis it was possible to verify that the frozen oyster was satisfactorily accepted for the human consumption, with situated indices of acceptability above of 70%.